Gelddinge: Doing Money in der ersten Hälfte des 20. Jahrhunderts - Derix, Simone (Historische Anthropologie, 2019)
This article highlights the need to intensify the research on money practices in contemporary history by concentrating on their material dimensions. Therefore, the analysis explores two different fields of „doing money“ in the first half of the 20th century that have been largely neglected so far. Firstly, it focuses on the attempts to establish cashless payment in Germany and discusses cheques as alternative means of payment to coins and banknotes. Secondly, it examines the measures taken to pro-tect money from forgery and theft and the associated fascination with quartz lamps, safes and safecrackers.
CRIS-Team Scopus Importer:2023-03-21